Effectiveness of drug-coated balloon in treating real-world femoropopliteal lesions: A cohort study - Guochen Niu; Bihui Zhang; Ziguang Yan; Yinghua Zou; Xiaoqiang Tong; Min Yang (Vascular Investigation and Therapy, 2023)
BACKGROUND: The drug-coated balloon is superior to angioplasty for simple femoropopliteal lesions in clinical trials. The evidence on the effectiveness of Acotec drug-coated balloon in treating complex femoropopliteal lesions in the real world is limited. This study aimed to investigate the clinical effectiveness of Acotec drug-coated balloon in real-world femoropopliteal lesions. METHODS: The retrospective study enrolled 128 limbs of 120 patients treated with the Acotec drug-coated balloon in femoropopliteal lesions. Patency rate, target lesion revascularization (TLR) rate, clinical improvement, and safety endpoints of femoropopliteal lesions were analyzed for a 12-month follow-up. Risk factors of primary patency and freedom from TLR were identified. RESULTS: Of the limbs, 31.2% had chronic limb-threatening ischemia. The mean lesion length was 199.3 ± 108.9 mm, and 75.8% were occlusions. Kaplan–Meier estimates of 12-month primary patency were 88.5%, whereas freedom from TLR rate was 95.2%. Rutherford category improved in 87.1% of patients. Freedom from 30-day major adverse limb events was 95.5%. The 12-month overall mortality was 8.6%. No independent risk factors for restenosis and TLR were identified. CONCLUSIONS: The results suggest that Acotec drug-coated balloon is safe and effective in treating complex femoropopliteal artery diseases in the real world.